Assessment of restorative treatment of patients with amelogenesis imperfecta - Chen, Chiung-Fen; Hu, Jan Ching Chun; Estrella, Maria Regina Padilla; Peters, Mathilde C.; Bresciani, Eduardo [UNESP] (My University, 2013)
Purpose: The purpose of this study was to assess restorative treatment outcomes in the mixed dentition of amelogenesis imperfecta (AI) patients and determine the postrehabilitation oral health status and satisfaction of the patients. Methods: Clinical and radiographic examinations were performed on eight AI patients, who had 74 restorations placed in permanent incisors and molars, to allow evaluation of the integrity of the restorations and periodontal status post-treatment. Subjects completed a survey regarding esthetics, function, and sensitivity. Results: Among the 74 restorations evaluated, seven were lost; of the remaining restorations, 31 were posterior, and 36 were anterior. Ten were rated clinically unacceptable. Teeth with stainless steel crowns had a moderate gingival index (mean=2.3) and plaque index (mean=2.0) scores. Widening of the periodontal ligament and pulp canal obliteration were common radiographic findings. Subject's recall of satisfaction regarding esthetics (P=.002) and sensitivity (brushing-P=.03; eating-P=.01) showed a statically significant difference before and after treatment. Conclusions: During mixed dentition, teeth with amelogenesis imperfecta may be restored with conventional treatment modalities. Direct restorations should be considered interim with multiple repairs anticipated. Post-treatment, gingival inflammation and plaque accumulation were observed. Subjects were satisfied with their appearance and reported a decrease of hypersensitivity. © 2013 Publishing Technology.
Keywords: Mixed dentition; Oral health; Restorative treatment; Treatment outcome